1996
DOI: 10.1074/jbc.271.19.11204
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Nitric-oxide Synthase-μ, an Alternatively Spliced Isoform Expressed in Differentiated Skeletal Muscle

Abstract: Nitric oxide (NO) functions as a molecular mediator in numerous processes in cellular development and physiology. Differential expression and regulation of a family of three NO synthase (NOS) gene products help achieve this diversity of action. Previous studies identify post-translational modification and interaction of NOS with specific protein targets as tissue-specific modes of regulation. Here, we show that alternative splicing specifically regulates neuronal NOS (nNOS, type I) in striated muscle. nNOS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
208
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(215 citation statements)
references
References 28 publications
(33 reference statements)
6
208
0
1
Order By: Relevance
“…12,13 We have found that these two isoforms exist in different proportions in the lower urinary tract, skeletal muscle and the penis. In this study, we found a signi®cant down-regulation of only the large form of nNOS in the diabetic rats but not the small form.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 We have found that these two isoforms exist in different proportions in the lower urinary tract, skeletal muscle and the penis. In this study, we found a signi®cant down-regulation of only the large form of nNOS in the diabetic rats but not the small form.…”
Section: Discussionmentioning
confidence: 99%
“…The increases in intracellular Ca 2+ that occur upon muscle excitation increase basal nNOS activity several fold during contraction . Skeletal muscles express two alternatively spliced nNOS isoforms, nNOSμ and nNOSβ, both of which are expressed in fast and slow muscle types (Silvagno et al 1996;Stamler and Meissner 2001;Percival et al 2010, Figure 1). nNOSμ is scaffolded to the subsarcolemmal dystrophin glycoprotein complex (DGC) and neuromuscular junction (Brenman et al 1995(Brenman et al , 1996Adams et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Transcripts resulting from the alternative splicing of a gene are not an uncommon occurrence. For example, the constitutive forms of the hemoprotein, NO synthase [9-111 in the brain and muscle are the products of alternatively spliced transcripts and differ only by a short sequence of internal amino acids [12]. Also, we were inquisitive as to whether there exist additional form(s) of HO in biological systems, as is the case with many heme-related proteins.…”
mentioning
confidence: 99%